Children's proximity and non-family support to elderly adults in Europe - Agnieszka Fihel; Małgorzata Kalbarczyk; Anna Nicińska (University of Warsaw, Centre of Migration Research (CMR), 2019)
Geographical distance between adult children and elderly parents adversely affects the provision of help to the latter. We investigate how neighbours, friends and other non-family individuals compensate for the shortages of help received by elderly persons. On the basis of SHARE data for twelve European countries, we estimate the probability and amount of unpaid support received by persons aged 65 and over living at different distances to their children. Parents living in the proximity rely almost exclusively on family; as the geographical distance between adult children and elderly parents increases, the probability and amount of non-family support increase as well. In eastern and southern Europe, elderly individuals receive more support from both family and non-family than their counterparts in western and northern Europe. Non-family supporters compensate for the absence of children in the proximity, but the engagement of the former depends strongly on cultural and institutional conditions.
Keywords: 330; intergenerational relations; elderly people; support; support networks; childlessness